Urgensi Penggunaan Closed Circuit Television (CCTV) Dalam Mengungkap Tindak Pidana Pencurian - Sauqi M Rohit (Fakultas Hukum Universitas Andalas, 2023)
Technological developments have a positive role in handling and preventing crime in Indonesia, one of which is CCTV. This role is most relevant if it is related to criminal acts or theft crimes that occur in society. This article discusses the role of technology, especially CCTV, in disclosing criminal acts of theft. The research method used is normative juridical with a statutory approach and a legal concept approach in the form of law enforcement theory. CCTV has proven to be a very effective tool in uncovering crimes by recording incidents accurately and objectively, providing strong evidence at every stage of law enforcement, and even preventing criminal acts by making perpetrators feel watched. Legally, CCTV can be used as evidence or at least as an indication of the theft that occurred so that it is easier to find the perpetrator